Efficacy in myopia control - Brennan, Noel A.; Toubouti, Youssef M.; Cheng, Xu; Bullimore, Mark A. (Progress in retinal and eye research, 2021)
There is rapidly expanding interest in interventions to slow myopia progression in children and teenagers, with the intent of reducing risk of myopia-associated complications later in life. Despite many publications dedicated to the topic, little attention has been devoted to understanding ‘efficacy’ in myopia control and its application. Treatment effect has been expressed in multiple ways, making comparison between therapies and prognosis for an individual patient difficult. Available efficacy data are generally limited to two to three years making long-term treatment effect uncertain. From an evidence-based perspective, efficacy projection should be conservative and not extend beyond that which has been empirically established. Using this principle, review of the literature, data from our own clinical studies, assessment of demonstrated myopia control treatments and allowance for the limitations and context of available data, we arrive at the following important interpretations: (i) axial elongation is the preferred endpoint for assessing myopic progression; (ii) there is insufficient evidence to suggest that faster progressors, or younger myopes, derive greater benefit from treatment; (iii) the initial rate of reduction of axial elongation by myopia control treatments is not sustained; (iv) consequently, using percentage reduction in progression as an index to describe treatment effect can be very misleading and (v) cumulative absolute reduction in axial elongation (CARE) emerges as a preferred efficacy metric; (vi) maximum CARE that has been measured for existing myopia control treatments is 0.44 mm (which equates to about 1 D); (vii) there is no apparent superior method of treatment, although commonly prescribed therapies such as 0.01% atropine and progressive addition spectacles lenses have not consistently provided clinically important effects; (viii) while different treatments have shown divergent efficacy in the first year, they have shown only small differences after this; (ix) rebound should be assumed until proven otherwise; (x) an illusion of inflated efficacy is created by measurement error in refraction, sample bias in only treating ‘measured’ fast progressors and regression to the mean; (xi) decision to treat should be based on age of onset (or refraction at a given age), not past progression; (xii) the decreased risk of complications later in life provided by even modest reductions in progression suggest treatment is advised for all young myopes and, because of limitations of available interventions, should be aggressive. •Axial length is the preferred metric for monitoring progression of myopia.•Efficacy of myopia control treatments should be expressed as absolute, not percentage, effect.•Efficacy of treatments tends to be independent of age, progression rate and initial refractive error but not time.•Myopia control treatment efficacy is not as good as previously thought.•Past progression is not a good indicator of future progression and all myopic children aged 12 and under should be treated and treated aggressively.